Experimentando Arquiteturas de Internet do Futuro com Internet das Coisas - Chaib, Ramon Pereira dos Santos (2018)
In the last decade, many approaches emerged to revolutionize Internet architecture from scratch. They are collectively called Future Internet Architectures. In this work, we address the challenge of experimenting with Internet of things in this context. Using open-source tools,we developed a standard scenario capable to evaluate proposals in a small scale rst (locally,in laboratory), and latter in large scale cloud-based testing platform. As a use case of the proposal, we discuss its application to the eXpressive Internet Architecture, including implementation details, bringing performance results to laboratory-run tests.